Tingkat Kepuasan Pasien Bpjs Rujuk Balik Terhadap Pelayanan Informasi Obat Di Apotek Budi Sehat Bantul Yogyakarta - Fitria Dhirisma (Program Studi Farmasi UNAJA, 2022)
Abstract Background: Drug Information Services is an important part of pharmaceutical services at pharmacies because it is the main factor in good drug use and is expected to reduce or even avoid the possibility of errors in drug delivery or use. Objective: To determine the level of satisfaction of BPJS patients for referral to drug information services at Budi Sehat Pharmacy Bantul. Method: The type of research is descriptive observational with number of samples were 80 respondents who were taken from BPJS Referral patients who came to Budi Sehat Pharmacy Bantul to take drugs that had met the inclusion. Data analysis was carried out using the ServQual method. Results: Tangible dimension in the fairly satisfied category (0.75), the reliability dimension in the very satisfied category (0.87), the Responsiveness dimension in the very category. satisfied (0.86), dimension assurance (assurance) category very satisfied (0.90), dimension Empathy (emphaty) category very satisfied (0.91). Conclusion: the level of satisfaction at the Budi Sehat Pharmacy Bantul regarding drug information services to BPJS referral patients obtained a satisfaction level in the very satisfied category (0.85).